The value of IgG to IgM ratio in predicting secondary dengue infection - I Putu Gede Karyana; Hendra Santoso; Bagus Ngurah Putu Arhana (Indonesian Pediatric Society, 2006)
Background The determination of primary or secondary dengueinfection using hemagglutination inhibition (HI) test is time-con-suming. The IgG to IgM ratio which can be obtained earlier wasused by several studies to differentiate secondary from primaryinfection, but they still reported various cut-off points.Objective To find the diagnostic value and best cut off point ofIgG to IgM ratio for predicting secondary dengue infection.Methods This was a prospective study carried out between July2003 and June 2004. Children with suspected dengue hemor-rhagic fever (DHF) were tested for HI during acute and convales-cent phase. The IgG and IgM titer were examined during the acutephase using ELISA method.Results Sixty-two children were recruited, 48 with secondary in-fection and 14 with primary infection. The prevalence of second-ary infection was 77%. The best cut off point of the IgG to IgM ratioto predict secondary infection was >1.1 with sensitivity of 87.5%,specificity 92.9%, likelihood ratio 12.3, and post test probability97.7%.Conclusion The IgG to IgM ratio of >1.1 is a good predictor forsecondary infection